Radiofrequency Ablation of Drug‐Resistant Cancer Cells Using Molecularly Targeted Carboxyl‐Functionalized Biodegradable Graphene. Issue 5 (13th January 2015) - Sasidharan, Abhilash; Sivaram, Amal J.; Retnakumari, Archana P.; Chandran, Parwathy; Malarvizhi, Giridharan Loghanathan; Nair, Shantikumar; Koyakutty, Manzoor
<x xml:space="preserve">Abstract</x> Under ultralow radiofrequency (RF) power, transferrin‐conjugated graphene nanoparticles can thermally ablate drug‐ or radiation‐resistant cancer cells very effectively. The results suggest that graphene‐based RF hyperthermia can be an efficient method to manage drug‐/radiation‐resistant cancers. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>